She trades, because she can - Vanessa Erogbogbo (International Trade Forum, 2016)
Stephen Elop, the former Microsoft executive, said on the takeover of Finnish mobile-device maker Nokia a couple of years ago that ‘we didn’t do anything wrong, but somehow, we lost’.